(3EHGfI GdefGgL aj fUjMI GdNhGQLs - (3GdbGVi TeS GdOjf LYaQ Hf CMeO Hf YHO GdSdGe GdjeGfi GdRjOis
(3ChdgG (B:s
(3GdMeO ddg GdbGFe Ydi faS HeG cSHJ s
(3BNQgG (B:s
(3afSCd Gddg SHMGfg Cf jLYdfG ef GdbGPajf HGdMb Ydi GdHGWd hMSHfG Gddg hcai hfYe Gdhcjd hfYe Gdehdi hfYe GdeUjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3ai HjGf ebGdGJ GdNhGQL hGdQO YdjgGs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3GdJhMjO hGdedd hGdfMds